Waqf Property: Developing Innovative Utilization Model - Hashim, Suraiya; Maamor, Selamah; Abd Mutalib, Hasyeilla; Abd Wahab, Norazlina; Zainol, Zairy; Shakrani, Mohd Saharudin (UUM, 2021)
Waqf is one of the benevolence charities that are highly encourage in Islam. Through the donated waqf property, the benefit will provide to all of the beneficiaries directly or indirectly. Thus, all waqf property should be managed and administered efficiently. A good and effective institutional Mutawalli is capable not only to develop but also to utilize the property. However, most institutional Mutawalli facing challenges in their governance practices, hence these properties are not being utilized to achieve their full impact to other beneficiaries. Therefore, the aim of this study are; (1) to understand the current utilization of waqf property among the institutional Mutawalli in Malaysia; (2) to explore the governance practices among institutional Mutawalli; and (3) To proposed waqf property utilization model by incorporating the thematic data among the institutional Mutawalli in Malaysia. A qualitative method applied in this study by using multiple case studies with purposive sampling where formal and semi-structured interview conducted to the selective representative of institutional Mutawalli. The participants are those in leadership positions such as CEO and the top management of the institutional Mutawalli from various types of waqf institutions such as government, semi-government, corporate/private and trustee board institution. Significant output from this study includes (i) Focusing on difference types of institution will reflect different implementation of waqf property utilization in Malaysia. (ii) The proposed waqf property utilization model which could assist Malaysian government in its economic transformation program especially in waqf property. The model capable to identify the crucial characteristic in the waqf property which needs to possess and/or reduce the gaps so that Malaysia has similar characteristic in utilizing the waqf property with other success countries. (iii) The proposed utilization model could benefit the policy makers, institutional Mutawalli and development strategies across the globe to clearly identify the important interdependent characteristics and assist them to undertake and structural changes and help them attain growth performance.